2012
DOI: 10.1021/je3006612
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of Zdanovskii’s Rule for Predicting the Water Activity of Multicomponent Aqueous Strong Electrolyte Solutions

Abstract: The effectiveness of Zdanovskii's rule as a fundamental method of predicting water activities in mixed aqueous strong electrolyte solutions has been investigated. Unfortunately, when literature data available for more than 100 ternary systems (i.e., two electrolytes plus water) were examined, sufficient measurements were rarely available to test Zdanovskii's rule conclusively. This is because few mixed systems have been studied by more than one (independent) investigator and, in these few cases, the difference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 132 publications
0
17
0
Order By: Relevance
“…This paper describes the current stage of development of JESS in the context of chemical speciation modelling. It deals in particular with general equilibrium calculations by JESS based on chemical reaction thermodynamics rather than its other features which are concerned with the physicochemical properties of strong electrolytes (May et al, 2010;Rowland and May, 2010;May et al, 2011;Rowland and May, 2012;Rowland and May, 2013). Two large chemical speciation calculations using JESS (Version 8.3) will be described, one of synthetic seawater and the other of the low-molecular-weight components in human blood plasma.…”
Section: Introductionmentioning
confidence: 99%
“…This paper describes the current stage of development of JESS in the context of chemical speciation modelling. It deals in particular with general equilibrium calculations by JESS based on chemical reaction thermodynamics rather than its other features which are concerned with the physicochemical properties of strong electrolytes (May et al, 2010;Rowland and May, 2010;May et al, 2011;Rowland and May, 2012;Rowland and May, 2013). Two large chemical speciation calculations using JESS (Version 8.3) will be described, one of synthetic seawater and the other of the low-molecular-weight components in human blood plasma.…”
Section: Introductionmentioning
confidence: 99%
“…The effectiveness of Zdanovskii's rule has been evaluated for many electrolytes, with wide success. [46][47][48][49] Given that Zavitsas' model ensures that mixtures will obey Zdanovskii's rule, the success of Zdanovskii's rule to a wide variety of electrolytes may indicate that Zavitsas' model will work for those multicomponent electrolyte systems as well.…”
Section: Zdanovskii's Rule and Zavitsas' Modelmentioning
confidence: 99%
“…Rowland and May showed that Zdanovskii's rule does not always hold when the water activity of the mixture is being extrapolated outside the range of the binary systems. 49 Zhou et al showed…”
Section: Zdanovskii's Rule and Zavitsas' Modelmentioning
confidence: 99%
“…, they can be used to check for careless mistakes, they can impose thermodynamic conformance, they can take advantage of thermodynamic redundancy to improve reliability, and they can be easily applied to smooth and unify experimental data, by averaging and other numerical methods. The limitations of data derived from a single laboratory, no matter how reputable, are increasingly being appreciated and their implications better understood. We have noted a particularly valuable feature of precise empirical equations such as those of Pitzer and Hückel (which often give closely similar results for various thermodynamic functions) for unifying data from multiple sources (Figure ) and identifying systematic errors. This is because any differences in fitting often just reflect the functions’ different sensitivities to error.…”
Section: Promising Recent Developmentsmentioning
confidence: 99%
“…This is because any differences in fitting often just reflect the functions’ different sensitivities to error. Elimination of experimental outliers in mixed solutions of strong electrolytes has also been made much easier by the systematic corroboration and subsequent application of so-called “linear mixing rules”. , …”
Section: Promising Recent Developmentsmentioning
confidence: 99%